2017
DOI: 10.4103/2249-4863.214987
|View full text |Cite
|
Sign up to set email alerts
|

Does violence affect the use of contraception? Identifying the hidden factors from rural India

Abstract: Purpose:The objective of this study is to investigates the relationship between domestic violence and use of contraception among married women in rural India.Data:Third round of National Family Health Survey (NFHS-III).Methodology:Cross tabulation as bivariate analysis and Binary Logistic Regression as multivariate analysis has been employed to fulfill the objective.Findings:The result shows that there are several hidden factors. between physical violence and contraception use. Alternate explanatory variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Another case-controlled study showed that inter partner violence was reported by almost a third (29%) of women seeking to terminate pregnancy and a quarter (22%) seeking contraceptive counselling ( Öberg et al., 2014 ). In India, the level of education and awareness as well as women empowerment could influence physical violence in regards to the use of contraception ( Singh and Shukla, 2017 ). In Sweden, 27% of women with low educational level seeking FP services experienced sexual violence ( Öberg et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another case-controlled study showed that inter partner violence was reported by almost a third (29%) of women seeking to terminate pregnancy and a quarter (22%) seeking contraceptive counselling ( Öberg et al., 2014 ). In India, the level of education and awareness as well as women empowerment could influence physical violence in regards to the use of contraception ( Singh and Shukla, 2017 ). In Sweden, 27% of women with low educational level seeking FP services experienced sexual violence ( Öberg et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is suitable for eliminating problems, especially if the problem is related to physical, mental, social and cultural health, the medical team and one of its important pillars, the nurse, can use the results due to its close relationship with society. [ 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…(Puducherry; South India, 2015), and Singh and Shukla (NFHS-3). [1141516] This might be because education can change the way of thinking. Alcoholic husband was a risk factor in both types of domestic violence.…”
Section: Discussionmentioning
confidence: 99%